New records of Anacroneuria Klapálek, 1909 (Plecoptera: Perlidae) for Central America - Gutiérrez-Fonseca, Pablo E.; Alonso-Rodríguez, Aura M.; Cornejo, Aydeé; Bailey, Anna Cristina; Maes, Jean-Michel; Ramírez, Alonso (Zootaxa, 2015)
The perlid genus Anacroneuria is the most widely distributed stonefly occurring in the Neotropics. Regional studies of this genus were made early in the last century, whereas local taxonomic and distributional studies have recently increased. In this study, we provide new Central American records for four species of Anacroneuria. Anacroneuria choco Stark & Bersosa 2006, A. costana (Navás 1924), A. hacha Stark 1998, and A. laru Gutiérrez-Fonseca 2015 are newly reported including new range extensions.